The Role of Population, Inflation and Economic Growth of Local Tax Revenues in East Java Province, Indonesia - Puspita, Yeni (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to determine the influence between population, inflation, and economic growth on local tax revenues and find appropriate policy strategies in maximizing local tax revenues in Java province East. This research uses secondary and primary data with interviewees. The data analysis method uses a quantitative approach using multiple linear regression analyses. The results of this research are variable inflation and economic growth do not affect local tax revenues. Only a variable population has a significant effect on local tax revenues, meaning that if the population increases the local tax revenues are also increased. Likewise, if the population decreases, the number of local tax revenues decreases. When tested simultaneously, the number of population variables, inflation, and economic growth have a significant influence on the local tax of 41%.